2021
DOI: 10.1177/00157325211021503
|View full text |Cite
|
Sign up to set email alerts
|

Impact of India-ASEAN Free Trade Agreement: An Assessment from the Trade Creation and Trade Diversion Effects

Abstract: This article investigates the impacts on the India–Association of Southeast Asian Nations (ASEAN) Free Trade Agreement (IAFTA) on trade creation and trade diversion. The gravity model is employed, where multilateral resistance terms are included. A panel data set of 45 countries that included India, ASEAN-10 nations and India’s top 34 trading partners in 2018 were used for the period from 1996 to 2018. The article explored that IAFTA leads to a trade creation in total bilateral trade in terms of exports and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Yang and Martinez-Zarzoso (2014) also reported the ASEAN–China Free Trade Agreement (ACFTA) has substantial and significant trade creation effects in the case of both agricultural and manufactured goods. Similar results were found by Singh (2021) using India–Association of Southeast Asian Nations (ASEAN) Free Trade Agreement (IAFTA). A study by Tegebu and Seid (2019) analysed the effect of African RTAs on strategic agricultural products and found that the RTAs have mixed effect on trade creation and trade diversion with SADC having no net creation or diversion effect.…”
Section: Results Presentation and Analysissupporting
confidence: 86%
“…Yang and Martinez-Zarzoso (2014) also reported the ASEAN–China Free Trade Agreement (ACFTA) has substantial and significant trade creation effects in the case of both agricultural and manufactured goods. Similar results were found by Singh (2021) using India–Association of Southeast Asian Nations (ASEAN) Free Trade Agreement (IAFTA). A study by Tegebu and Seid (2019) analysed the effect of African RTAs on strategic agricultural products and found that the RTAs have mixed effect on trade creation and trade diversion with SADC having no net creation or diversion effect.…”
Section: Results Presentation and Analysissupporting
confidence: 86%
“…Anderson and van Wincoop (2003) also present an augmented version of Anderson’s (1979) gravity model which includes addition of multilateral resistance terms for the exporter and importer that proxy for the existence of undetected trade barriers. The discussion of multilateral resistance matters for heteroscedasticity considerations (Singh, 2021), a topic not addressed by many trade models, makes this model intriguing overall. Using the Poisson Pseudo Maximum Likelihood (PPML) technique with the gravity model in this study also solves the issue of zero trade flows and heteroscedasticity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…India is keen on capitalising on the significant growth potential presented by Southeast Asian nations and reducing its import reliance on other countries, especially China (Singh, 2021). Recent scholarly literature emphasises that the integration of South Asia and East Asia could yield substantial economic benefits for both regions, particularly through deeper value chain integration.…”
Section: Introductionmentioning
confidence: 99%